The Significance of Isomerism and Complexity of Composition, on the Performance of Triaryl Phosphate Plasticisers in PVC - Angus J. Duke (CHIMIA)
The effectiveness, as PVC plasticisers, of alkylsubstituted triaryl phosphates of various isomer distributions and increasing degrees of complexity of composition, are assessed. The complexity factors in such mixture products include molecular symmetry / dissymmetry, relative distribution of substituted aryl groups between phosphate molecules, substituent positional isomerism, extent of concurrent polysubstitution on the aryl groups, and ultimately contributions of alkyl substituents of different sizes. The most important factors are shown to be substituent positional isomerism, coupled with degree of (mono)-substitution. This applies both for physical properties, such as plasticiser efficiency and especially low temperature flexibility, and the partially correlated fluid viscosity properties, and also for chemically-controlled stabilities, e.g. colour stability, compatibility in light. Secondary, but still important, factors are content of poly-substituted aryl groups, and distribution of substituent content between phosphate molecules – this latter primarily to ensure adequate low temperature fluidity of the liquid plasticiser. Poly-substituted content also appears to have some positive effect on light stabilities. Meta isomer contents, at least of methyl, ethyl or isopropyl groups, give very favourable effects on low temperature flexibilities. However, significant meta contents result in severe deterioration of the colour stabilities and compatibilities of PVC compositions. The preferred substituent type is shown to be orthoisopropyl, accompanied by substantial levels of unsubstituted phenyl groups, and a small content of polysubstitution.